Merrill, Thomas W. The Chevron Doctrine: Its Rise and Fall, and the Future of the Administrative State - Adler, Jonathan H. (Journal of Economic Literature, 2025)
Jonathan H. Adler of William and Mary Law School reviews “The Chevron Doctrine: Its Rise and Fall, and the Future of the Administrative State” by Thomas W. Merrill. The Econlit abstract of this book begins: “Explores the standard that courts apply in determining whether an administrative agency has correctly interpreted the statute under which it operates, delving into where this standard – the Chevron doctrine – came from, how it spread, and arguments over its adequacy.”